Relatedness needs satisfaction or ego depletion? The effect of leisure nostalgia on life satisfaction - Li, Dan; Xi, Juzhe; Xu, Yeran; Song, Aifen; Shi, Yanwei (Frontiers in Psychology, 2025)
BackgroundPrevious studies focused on the positive aspects of leisure nostalgia in relation to positive outcomes, overlooking its negative aspects and the possibility of negative effects. Based on the basic psychological needs theory and self-regulation theory, we tested whether relatedness need satisfaction and ego depletion mediated positive and negative effects of leisure nostalgia, respectively, and whether these mediation processes were moderated by self-regulatory capacity.MethodsWe collected two waves of questionnaire data with a 1-month interval from 391 university students. The instruments used in this study included demographic characteristics and questionnaires of ego depletion, leisure nostalgia, life satisfaction, relatedness need satisfaction, self-regulatory capacity. Data analysis was performed using the SPSS and Mplus.ResultsLeisure nostalgia was positively related to university student life satisfaction via higher relatedness need satisfaction (indirect effect = 0.11, 95% CI [0.052, 0.161]), and this indirect effect was stronger for students with higher vs. lower self-regulatory capacity (index = 0.03, 95% CI [0.003, 0.062]). By contrast, the mediating effect of ego depletion in the relationship between leisure nostalgia and lower life satisfaction was not significant (indirect effect = −0.01, 95% CI [−0.020, 0.011]).ConclusionsFindings from this study suggest that leisure nostalgia is a predominantly positive emotional experience that can promote university students' life satisfaction. The results have practical implications for designing programs to enhance university students' leisure nostalgia, self-regulation capacity, and life satisfaction.